A prospective pilot study of antibodies against human papillomaviruses and cutaneous squamous cell carcinoma nested in the Oxford component of the European Prospective Investigation into Cancer and Nutrition. - Casabonne, D; Michael, K; Waterboer, T; Pawlita, M; Forslund, O; Burk, R; Travis, R; Key, T; Newton, R (2007)
In a prospective pilot study nested in the EPIC-Oxford cohort, we examined the seroprevalence of antibodies against the L1 antigen of 38 human papilloma virus (HPV) types among 39 cases of cutaneous squamous cell carcinoma (SCC) for whom plasma was collected prior to diagnosis (incident) and 80 controls. Fifteen cases having already developed SCC at blood collection (prevalent) were also tested. There were no statistically significant differences in the seroprevalence of antibodies against any of the HPV types examined between incident cases and controls, nor was there a difference in the seroprevalence of multiple infections. However, consistent with results from published case-control studies, the seroprevalence of many beta-HPV types was higher among prevalent cases than among either incident cases or controls. For example the seroprevalence of antibodies against HPV-8 was 20% (16/80) in controls, 23% (9/39) among incident cases and 40% (6/15) among prevalent cases. Among the incident cases only, the seroprevalence was 16% (5/32) among those for whom blood was collected 18+ months prior to diagnosis, but 57% (4/7) among those for whom diagnosis was within 18 months of blood collection, a pattern seen for many of the HPV types. This might suggest that if HPV is involved in the aetiology of SCC, the process occurs close to the time of diagnosis, or that the antibody response observed in people with SCC is a consequence of tumor formation. Further and larger prospective studies are needed to clarify the role of HPV in the aetiology of cutaneous SCC.